Sex as a moderator in the associations between psychopathy facets and aggressiveness - Sophie L. Kjærvik; Nicholas D. Thomson; Nicholas D. Thomson (Frontiers in Psychology)
IntroductionPsychopathy reliably predicts aggression, making it valuable for violence prevention. However, research on sex differences within the 4-facet model, which includes affective, interpersonal, lifestyle, and antisocial facets of psychopathy, is limited, especially among high-risk community samples.MethodsThis study examined sex differences in the psychopathy facets associated with anger, hostility, and aggression among 419 (Mage = 32.6, 72% male) violently injured adults. Studying high-risk, non-institutionalized individuals offers unique insights into the link between psychopathy and aggression, particularly in real-word context where institutional influences are absent. Participants completed the Self-Report Psychopathy and Aggression Questionnaire.ResultsHierarchical multiple regressions revealed that all four facets predicted physical and proactive aggression; affective, lifestyle, and antisocial facets were related to reactive aggression; and affective and lifestyle facets were related to anger, hostility, and verbal aggression. Sex moderated relations between psychopathy facets and anger and hostility. Specifically, the affective facet was associated with anger and hostility for males but not for females. The lifestyle facet was associated with anger and hostility for males and females, but the effect was stronger for females.DiscussionThe findings indicate that the four-facet model relates to aggressive emotions and cognition differently for males and females, while demonstrating consistency in physical and verbal aggression. Recognizing that psychopathic anger and hostility are sex-specific can improve violence interventions tailored to males and females.